PERSEPSI GURU TENTANG KOMPETENSI SUPERVISI KEPALA SEKOLAH SD NEGERI KECAMATAN PADANG TIMUR KOTA PADANG - Ira Syafmawati (Jurnal Bahana Manajemen Pendidikan, 2013)
This study aims to determine teachers' perceptions of supervision competency the headmaster. This is a descriptive study. The population is 291 teachers and the sample is 137 people that taken by Cluster random sampling.. In general, teachers' perceptions of the supervision competency of headmaster elementary school Kecamatan East Padang of Padang city. Determine teacher’s perception of supervisiom competence the headmaster taken average score overall was 80.2%. From the research it can be said that Supervision Competency of headmaster Elementary School kecamatan east Padang in Padang city is good. Key word; Supervision competency of headmaster